Role of aluminum chloride on the reversible hydrogen storage properties of the Li-N-H system - Fernández Albanesi, Luisa Francisca (2015)
In order to understand the role of AlCl3 addition on the Li-N-H system, we have systematically investigated the hydrogen sorption kinetics and the reactions between LiNH2-LiH and AlCl3 additive with a multitechnique approach involving differential scanning calorimetry (DSC), hydrogen volumetric measurements, X-ray powder diffraction (XRPD), Fourier transform infrared analysis (FTIR) and solid-state nuclear magnetic resonance (NMR). Different interactions were identified as a function of the amount of added AlCl3. For low AlCl3 addition (0.03 mol), the Al3+ is incorporated into the interstitial sites by the LiNH2 structure. When AlCl3 amount increased (0.08 and 0.13 mol), the formation of new amide-chloride phases were detected by XRPD and indexed with cubic and hexagonal Li-Al-N-H-Cl geometries. Occurrence of such new phases was also confirmed by FTIR and NMR. The formation of these new Li-Al-N-H-Cl phases modifies the kinetics as well as the thermodynamic behavior of the original Li-N-H system. Interesting, in all AlCl3-doped composites, hydrogen was stored reversibly with faster sorption kinetics than un-doped Li-N-H system and with a significant reduction of NH3 emission. This improvement can be associated with the Al3+ incorporation into LiNH2 that promotes the migration of Li+, while for high AlCl3 doping, the formation of new phases Li-Al-N-H-Cl also weakens the N-H bond.